Subject tracking robotic manipulator using pan-tilt mechanism - Sulthana, S. Fouziya; Ashawise, Cross T.; Iqbal, U. Mohammed (AIP conference proceedings, 2022)
In this paper, the implementation of a real-time framework which can monitor RGB targets, with a fewer camera in a dynamic environment, is suggested. The applications which involve object tracking are quite crucial for military, surveillance system and operational robot applications and are becoming more significant gradually. The implemented design allows to track an object using fewer cameras. The three main parts of the design are object detection, mapping and tracking the object. When the camera captures the object, it first senses the color and applies different filters, and then detects the object's circular outline or boundary. And in accordance to the information obtained, an algorithm is used to calculate the centroid of the object. Object centroid is decided using coordinates of the circular boundary and then tracking process is initiated by activating the servo motors. The motors mounted on a robotic platform are called the pantilt platform, which is also roughly the spatial manipulator of the 2DOF. It can turn 270 degrees on x-axis and 180 degrees on y-axis. Viola-Jones algorithm was implemented for facial detection and tracking of the detected face with a PI control was designed.